Treatment of Primary Congenital Lymphedema Via the Godoy Method: A Case Report of 17-year Follow-up - Ana Carolina Pereira de Godoy; Jose Maria Pereira de Godoy; Rogerio Rodrigo Ramos; Maria de Fatima Guerreiro Godoy (Journal of Pediatrics Review, 2022)
The present research aimed to report the treatment of primary congenital lymphedema using the Godoy method with a 17-year follow-up period. A 2-month-old male patient with bilateral primary congenital lymphedema of the lower limbs was sent to the Clinica Godoy-Brazil for specialized treatment. The physical examination revealed bilateral lower limb edema affecting the feet and middle third of the legs. The patient was made to use hand-crafted stockings made of grosgrain fabric. When the child reached 10 years of age, mechanical lymphatic therapy was conducted. A considerable reduction in the edema was achieved but with periods of improvement and worsening. In the last 4 years of the 17 years of treatment, the limbs have remained within or near the range of normality. The present findings demonstrate that the Godoy method is effective in controlling edema in cases of primary congenital lymphedema. When the family has difficulties, others who take care of the child should get involved to ensure the treatment of this type of lymphedema.